Calling All Cars : Radio Dragnets and the Technology of Policing - Battles, Kathleen (Book collections on Project MUSE., 2010)
Calling All Cars shows how radio played a key role in an emerging form of policing during the turbulent years of the Depression. Until this time popular culture had characterized the gangster as hero, but radio crime dramas worked against this attitude and were ultimately successful in making heroes out of law enforcement officers. Through close analysis of radio programming of the era and the production of true crime docudramas, Kathleen Battles argues that radio was a significant site for overhauling the dismal public image of policing.